Ecohydrological gradients and their restoration on the periphery of extracted peatlands. Issue 4 (28th January 2019) - Lefebvre‐Ruel, Stéphanie; Jutras, Sylvain; Campbell, Daniel; Rochefort, Line
Abstract : The moss layer transfer technique is effective at restoring extracted peatland surfaces. However, remnant peatlands persist on the periphery of extracted surfaces. These remnant peatlands drop steeply to extracted surfaces, producing artificial ecotones that are more challenging to restore. We asked to what degree natural ecotones at undisturbed reference fens can act as models for the restoration of artificial ecotones around an extracted peatland, and whether management actions can ameliorate conditions in artificial ecotones. We compared changes in elevation, water table, peat, and multiple vegetation characteristics between natural ecotones and unmanaged artificial ecotones. We then clear‐cut peripheral strips, completely filled perimeter canals, and smoothed peripheral slopes around sections of the extracted surfaces to assess whether hydrological conditions improved. Without management, artificial ecotones are not good models of natural ecotones. The elevation gradient is steep, and water tables drop steeply within 8 m of blocked perimeter canals, with possible effects at 25 m. The consequent vegetation had denser tree saplings, faster tree growth, almost no moss cover, and low moss species richness. After these management actions, water tables increased to within approximately 5 cm of those along natural ecotones. Future study is required to assess the extent of vegetation recovery, but these results hold promise for a more holistic rehabilitation of ecotones on the periphery of extracted peatland surfaces. We present recommendations to optimize the management actions on the periphery of extracted peatlands.